Розробка біотехнологічних методів для відновлення чисельності деяких видів класу однодольних, що потребують охорони - Belokurova, V.B.; Szikura, A.J.; Szikura, J.J.; Kuchuk, N.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2004)
The possibility to use biotechnological methods for preservation and restoration of quantity of some preserved monocotyledonous species was studied by the example of Iris mandshurica Meissn. (Iridaceae), Juno kopetdagensis Vved. (Iridaceae) and Tulipa biflora Donn. (Liliaceae). The methods of introduction of these species into in vitro culture, formation of aseptic seedlings, of induction and cultivation of callus tissues and plant regeneration have been elaborated. Culture media compositions were established for obtaining of Iris mandshurica multiple shoots. The methods of plant regeneration via somatic embryogenesis from callus cultures of Juno kopetdagensis and Tulipa biflora have been created. Regenerated in vitro plants rooted in field conditions, formed flowers and seeds as well as vegetative progeny.